Allogeneic Hemopoietic Stem Cell Transplantation for Myelofibrosis: 2021 - Bacigalupo, Andrea; Innocenti, Idanna; Rossi, Elena; Sora, Federica; Galli, Eugenio; Autore, Francesco; Metafuni, Elisabetta; Chiusolo, Patrizia; Giammarco, Sabrina; Laurenti, Luca; Benintende, Giulia; Sica, Simona; et al. (Frontiers in Immunology, 2021)
The aim of this review is to update the current status of allogeneic hemopoietic stem cell transplants (HSCT) for patients with myelofibrosis. The manuscript will be divided in to the following sections. Indication for an allogeneic HSCT, as outlined in recent international guidelines. How to predict the outcome of HSCT, as suggested by prognostic risk scores, based on clinical, biological and transplant data. The choice of a transplant platform including the conditioning regimen, the stem cell source and GvHD prophylaxis. Poor graft function and graft failure. Monitoring disease control after HSCT with donor chimerism, driver mutations and hematologic data. Treatment of relapse. We have made an effort to make this review as comprehensive and up to date as possible, and we hope it will provide some useful data for the clinicians.